Initial assessment and monitoring of nutritional status and malignant pain in lung cancer patients - Karabatić, Sandra; Šajnić, Andreja; Čukljek, Snježana; Lukić Franolić, Ivana; Pleština, Sanja; Samaržija, Miroslav (2020)
Introduction. Lung cancer is a complex disease and requires a multidisciplinary approach to achieve the best results in treatment, to increase the survival rate while preserving the quality of life of the sufferer. The nutritional status of the patient is an important factor affecting outcome and recovery from disease or injury. We question whether there is a link between nutritional status and malignant pain in lung cancer patients. Aim. A prospective trial was conducted to determine the distribution of respondents by frequency of pain according to a validated Visual Analog Scale (VAS), distribution of respondents who reported reduced food intake and distribution of factors that have led to the reduced food intake. Methods. A prospective trial was conducted at the Department for respiratory diseases Jordanovac, University Hospital Center Zagreb, Croatia, on a sample of patients with advanced non-small cell lung cancer to determine the frequency, characteristics and treatment of chronic malignant pain (N=76). These are the results from November 2013 to June 2014. For pain assessment, we used a validated VAS. For the identification of patients at risk of malnutrition we used Nutritional risk screening tool (NRS 2002). For a rough estimate of total body adiposity, we measured dermal thicknesses using a standard calliper. Monitoring of patients was documented in the form of nursing documentation. A component of nursing documentation was designed to monitor the nutritional status of cancer patients and has been implemented at the Department for respiratory diseases Jordanovac as required documentation. The component included collecting the following data: the stage and type of cancer and treatment, demographic characteristics, age, gender, vital signs, body weight and height, body mass index (BMI), subjective symptoms such as pain, fatigue and nausea, reduction ad rezones of food consumption. Results.
Uvod. Rak pluća jest kompleksna bolest i zahtijeva multidisciplinarni pristup kako bi se postigli što bolji rezultati u liječenju i povećala stopa preživljavanja uz istodobno očuvanje kvalitete života oboljelog. Nutritivni status bolesnika pokazao se važnim čimbenikom koji utječe na ishod i oporavak od bolesti ili ozljede. Postavljamo pitanje postoji li poveznica između nutritivnog statusa i maligne boli u bolesnika s rakom pluća. Cilj. Provedeno je prospektivno istraživanje kako bi se utvrdila raspodjela ispitanika prema učestalosti bolova prema validiranoj vizualnoj analognoj skali (VAS), raspodjela ispitanika koji su prijavili smanjeni unos hrane i raspodjela čimbenika koji su doveli do smanjenog unosa hrane. Metode. Istraživanje je provedeno na Zavodu za tumore pluća i sredoprsja Klinike za plućne bolesti Jordanovac Kliničkoga bolničkog centra Zagreb, na uzorku bolesnika s uznapredovalim rakom pluća nemalih stanica (N = 76). u periodu od studenoga 2013. do lipnja 2014. Za procjenu boli primijenjen je validirani VAS. Za identifikaciju pacijenata s rizikom od pothranjenosti primijenjen je alat za provjeru prehrambenih rizika (NRS 2002). Za grubu procjenu količine masnog tkiva koristili smo se kaliperom. Praćenje bolesnika dokumentirano je u obliku sestrinske dokumentacije. Sastavnica sestrinske dokumentacije osmišljena je za praćenje prehrambenog stanja oboljelih od karcinoma i implementirana je na Odjelu za respiratorne bolesti Jordanovac kao potrebna dokumentacija. Sastavnica je obuhvatila prikupljanje sljedećih podataka: stadij bolesti i tip karcinoma, tip i stadij liječenja, demografske karakteristike ispitanika, debljina kožnog nabora, standardizirani upitnik o pothranjenosti Nutritional NRS 20021, vitalni znakovi, tjelesna težina, tjelesna visina, indeks tjelesne mase, subjektivna procjena pacijenta; bol, umor i mučnina, razlozi smanjene prehrane.
Bibliografija: 76 jed.
Abstract ; Sažetak.
Keywords: Rak pluća -- Nutritivni status -- Bol